(untitled) (Indian Journal of Animal Production and Management, 2017)
The present survey was undertaken to analyze the constraints faced by the urban and peri urban dairy farmers in around Hyderabad city of Telangana. A sample of 100 farmers (50 farmers each from Urban and Peri urban areas) was selected through simple random sampling technique. The data was analyzed by Henry Garret’s ranking technique. Twenty constrains were identified in the study. The study indicated that high cost of fodder and concentrates was perceived as a major problem (with a score of 76.19) followed by high cost of dairy animals as the second major constraint (with a score of 76.11) and high incidence of prolapse of uterus in dairy animals ( with a score of 23.09) was a twentieth constraint.